Penilaian Kinerja Sekretaris dalam Menerapkan Administrasi pada Kantor Pelayanan Kekayaan Negara dan Lelang Banda Aceh - Yurna Laina; M Djamil (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
This study aims to assess the performance of the secretary in implementing administration at the Banda Aceh State Property and Auction Service Office. The method used in this research is a qualitative approach with data collection techniques through interviews and observation. The results showed that the secretary's performance in implementing administration at the Banda Aceh State Property and Auction Service Office was quite good, although there were still some deficiencies such as a lack of understanding of the applicable regulations and there were still some errors in document filing. Factors that affect the performance of a secretary include technical skills, knowledge of rules and procedures, and communication skills. Therefore, it is recommended that the management provide training and development to secretaries to improve their technical skills and knowledge of regulations and improve the document filing system. Banda Aceh Country and Auction. In this study, factors such as expertise in document management, ability to organize schedules and agendas, and communication skills are the main factors in assessing the performance of a secretary. From the results of the data analysis, it was found that a secretary who has good administrative skills can increase work productivity and efficiency in the office. In addition, a secretary who can manage documents properly and effectively can reduce the risk of errors and lost documents that can interfere with office performance. However, the results of the study also show that there are still some secretaries who are less able to implement administration properly. Therefore, it is suggested that the Banda Aceh State Property and Auction Service Office provide regular training and competency development to secretaries so that they can continue to improve their administrative capabilities and performance.